SAT0253 ANTI-NEUTROPHIL CYTOPLASMATIC ANTIBODIES PREDATE SYMPTOM ONSET OF ANCA-ASSOCIATED VASCULITIS. A CASE-CONTROL STUDY. (2nd June 2020) - Berglin, E.; Mohammad, A. J.; Dahlqvist, J.; Eriksson, C.; Sjöwall, J.; Rantapää Dahlqvist, S.
Abstract : Background: Presence of anti-neutrophil cytoplasmatic autoantibodies (ANCA) is important for the diagnosis of ANCA-associated vasculitis (AAV) and reflects on-going immune processes. The timing of the antibody development and its contribution to disease is not well established. Objectives: To investigate the presence of proteinase 3 (PR3)- and myeloperoxidase (MPO)-ANCA in blood samples collected from healthy individuals who subsequently developed AAV. Methods: The Swedish National Patient Register of inpatient care and the Swedish Cause of Death Register were used to identify individuals assigned ICD codes for AAV (1) in the discharge summary or cause of death, respectively. The resulted cohort was then linked to the registers of 4 different biobanks to identify those with available predating blood samples. Diagnoses of AAV were confirmed and time point for onset of symptoms was identified by reviewing all available case records (1); 68 were classified as granulomatosis with polyangiitis (GPA), 14 as microscopic polyangiitis (MPA), and 4 as eosinophilic GPA (EGPA). The 86 cases (36 males, 50 females) had a mean (SD) age of 51.9 (16.9) years at sampling, with ≥1 sample (26% plasma, 74% serum samples). The sampling time point before onset of symptoms was mean (SD); 4.4 (3.1) years. Serum and plasma control samples (n=198; 82 males, 116 females; mean age (SD); 52.0 (16.5) years) were identified and matched for sex, age and date of sampling. The samples were first screened for ANCA using high sensitive ELISA (ORGANTEC diagnostika, Germany) and samples close to or above cut-off level were further analysed for capture PR3- and capture MPO-ANCA (ELISA; SVAR Life Science, Sweden). For each case one control sample was included for the ANCA specificity tests. Statistical calculations were performed using SPSS software. Results: In ANCA-screen 36.0% of the cases and 2.6 % of controls tested positive (p<0.001). 23/52 (44.2%) of the cases were PR3-ANCA positive (OR 56.3; 95% CI 7.26-436.62) and 8/52 (15.4%) were MPO-ANCA positive (OR 4.18; 95% CI 1.05-16.62). The mean (SD) predating time for PR3-ANCA positivity was 3.73 (3.49) years and for MPO-ANCA positivity 2.11 (1.46) years. Cases with positive predating PR3-ANCA were younger (46.0±19.4 vs 65.6±12.0 years; P<0.001) than cases with a negative predating PR3-ANCA. MPO-ANCA positive vs. MPO-ANCA negative pre-dating cases had more often severe disease (kidney/lung/peripheral nervous system) (OR 15.08; 95% CI 1.68—135.54) at disease onset. Furthermore, predating MPO-ANCA positive vs predating PR3-ANCA positive cases had significantly more often severe manifestations at disease onset (87.5% vs 28.6%; p<0.05). Cases positive vs. negative for MPO-ANCA in predating samples were less often classified as GPA (37.5% vs 86.4%; p<0.01) and more often as MPA (62.5% vs 13.6%; p<0.05). Conclusion: The production of both PR3 and MPO-ANCA starts already years before onset of symptoms of AAV. Presence of MPO-ANCA appeared closer to symptom onset and with more severe disease presentation. Differences in the disease phenotype and disease severity were evident between the two ANCA serotypes. References: [1]Watts et al. Ann Rheum Dis 2007;66:222-22 Acknowledgments: Vasculitis Foundation, USA Disclosure of Interests: Ewa Berglin: None declared, Aladdin J Mohammad Speakers bureau: lecture fees from Roche and Elli Lilly Sweden, PI (GiACTA study), Johanna Dahlqvist: None declared, Catharina Eriksson: None declared, Johanna Sjöwall: None declared, Solbritt Rantapää Dahlqvist: None declared